2017
DOI: 10.3390/technologies5040081
|View full text |Cite
|
Sign up to set email alerts
|

Design Optimization of Long-Span Cold-Formed Steel Portal Frames Accounting for Effect of Knee Brace Joint Configuration

Abstract: Abstract:The application of cold-formed steel channel sections for portal frames becomes more popular for industrial and residential purposes. Experimental tests showed that such structures with long-span up to 20 m can be achieved when knee brace joints are included. In this paper, the influence of knee brace configuration on the optimum design of long-span cold-formed steel portal frames is investigated. The cold-formed steel portal frames are designed using Eurocode 3 under ultimate limit states. A novel me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Column-to-rafter connections and rafter-to-rafter connections were assembled using eaves and apex joints, respectively, formed through plane brackets bolted between the webs of the channel-sections ( knee-to-column and knee-to-rafter connections can be reasonably considered as pinned joints [29,30], while moment connections with nine bolts used for apex joints were capable to carry bending moments [32]. It was also reported that rigid apex joints could be efficiently provided in the CFS portal frame by using bolt group length larger than 0.4 m [29,33]. In this study, it is assumed that the bolt group length is larger than triple of the beam depth, hence the effect of bi-moment caused by the presence of the bolts can be practically neglected [34][35][36].…”
Section: Frame Modelling and Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Column-to-rafter connections and rafter-to-rafter connections were assembled using eaves and apex joints, respectively, formed through plane brackets bolted between the webs of the channel-sections ( knee-to-column and knee-to-rafter connections can be reasonably considered as pinned joints [29,30], while moment connections with nine bolts used for apex joints were capable to carry bending moments [32]. It was also reported that rigid apex joints could be efficiently provided in the CFS portal frame by using bolt group length larger than 0.4 m [29,33]. In this study, it is assumed that the bolt group length is larger than triple of the beam depth, hence the effect of bi-moment caused by the presence of the bolts can be practically neglected [34][35][36].…”
Section: Frame Modelling and Analysesmentioning
confidence: 99%
“…To consider the design constraints for single objective optimisation in this study, an effective penalty approach [41,42] is applied, in which the penalised value for each violated design constraint is gradually decreased as the generation progresses [33,43]:…”
Section: Real-coded Genetic Algorithm (Rc-ga)mentioning
confidence: 99%
“…One possible situation is the combination of CFS roof truss with supporting structural system made of HRS section or reinforced concrete. The reasonable location of knee brace joint on the supporting structural system should be one-third of the eaves height from the top and knee angle is approximate 42° (Phan et al , 2017). By optimising the frame geometry and knee brace, configuration can noticeably improve the structural performance and reduce the required structural weight (Phan et al , 2020).…”
Section: Introductionmentioning
confidence: 99%